Front Cover: On the electrophoretic mobilities of partially charged oligosaccharides as a function of charge patterning and degree of polymerization. Issue 12 (19th June 2018) - Irani, Amir H.; Mercadante, Davide; Williams, Martin A.K.
Abstract : DOI:10.1002/elps.201800050 The cover picture shows the free solution electrophoresis of fully and partially charged oligosaccharides. Different species migrate differently owing to their size, nominal charge and the effects of counterion condensation. Molecular dynamics simulations allow the prediction of the elution order of species and capture the dependence of mobility on degree of polymerisation and ionic strength of the background electrolyte.